Genetic Polymorphisms and Their Association With the Prevalence and Severity of Chronic Postsurgical Pain: A Systematic Review. Issue 2 (April 2017) - Hoofwijk, D. M.; van Reij, R. R.; Rutten, B. P.; Kenis, G.; Buhre, W. F.; Joosten, E. A.
Abstract : (Abstracted from Br J Anaesth, 117(6):708–719, 2016) Several studies have been conducted to determine the risk factors for the development of chronic postsurgical pain (CPSP), which is common following any kind of surgery (prevalence of 10%–60%). Chronic postsurgical pain adversely affects the quality of life of patients and has significant socioeconomic impact.